GE_GERICHTE P/5166/2013 vom 4. Mai 2015 - GE Cour de justice (2015)
VIOLENCE DOMESTIQUE; INFRACTIONS CONTRE L'INTÉGRITÉ SEXUELLE; LÉSION CORPORELLE SIMPLE; CONTRAINTE(DROIT PÉNAL); TORT MORAL | CP.190.1; CP.22; CP.123; CP.186; CP.179septies; CP.181